Strategies of polemics in Greek and Roman philosophy - Weisser, Sharon.; Thaler, Naly, 1973- (Jerusalem Studies in Religion and Culture, 2016)
Strategies of Polemics in Greek and Roman Philosophy brings together papers written by specialists in the field of ancient philosophy on the topic of polemics. Despite the central role played by polemics in ancient philosophy, the forms and mechanisms of philosophical polemics are not usually the subject of systematic scholarly attention. The present volume seeks to shed new light on familiar texts by approaching them from this neglected angle. The contributions address questions such as: What is the role of polemic in a philosophical discourse? What were the polemical strategies developed by ancient philosophers? To what extent did polemics contribute to the shaping of important philosophical doctrines or standpoint?